Status of work accidents in food industry of Ukraine - Evtushenko, Olga; Klepikov, Igor (My University, 2013)
The aim of this work is carrying out of statistical analysis of occupational injuries among Food Industry employees. The object of research is occupational injury in Food Industry for 2003-2011 period. Status of occupational injury in Ukraine was analyzed for 2003-2011 period. We show a results of occupational injury dynamic research in Food Industry of Ukraine from 2003 to 2011 years. Distribution for male and female injured employees on enterprises of Food Industry was performed. Indexes of injury rate and heaviness were calculated. And finally, distribution of accidents for main reasons, sorts of events, profession group, age, work experience was performed. In recent years, industrial injuries, both general and fatal in Ukraine reduced. It is encouraging that this is happening at increasing production volumes and increased business. Despite the decline in Ukraine level, both general and fatal injuries, he remains unacceptably high and exceeds the performance of European countries. In order to establish the most significant and hazards that pose the highest risk of injury, when were analyzed by grouping indicators of injury accidents and fatalities by uniform signs, such as an event, cause, profession of the victim, and defined particle distribution of accidents for each feature . Determine the status, trends and magnitude of the problem of occupational injuries in the food industry, the laws and the impact of various factors on injuries. Established traumatic profession in some sectors of the food industry, revealed qualitative and quantitative parameters of reasons and factors that characterize the current state of injury by type of work performed, which makes this topic relevant. Exploration of labor safety conditions and also of occupational injury reasons and circumstances is useful for developing of sound and effective ways for prevent and reduce the occupational injury, illnesses and worker’s traumatism. The results of research shows, that in food industry of Ukraine during 2003-2011 the number of work accidents was decreased almost in 4 times. Big part of injuries accounted for experience workers who have service record over than 20 years and for workers with professional experience less than one year. We should to pay special attention during the primary and second instructing on the workplace. Besides, it is necessary to improve quality of instructing, intensify the control for low-skilled workers. It is necessary to enlarge the responsibility of all level directors on branch enterprises with aim to prevent the labor safety law violation which leads to work accidents. The frequency of injuries decreased, but the severity of injuries is still high. That means, the accidents became more dangerous. Average frequency of injuries Cf amounts 2.3 and severity of injuries index Cih amounts 34.3 – both of them for period from 2003 to 2011. It indicates that, despite decline of total number of accidents in food industry, the severity of injuries is increasing and it’s necessary to take crucial and complex measures for reduce these rates. Lately modern manufacture work in course international law of labor safety, where for rationale of prevention measures usually using a results of injury risk analysis. Choosing and reasoning of occupational injury prevention ways and measures is provided with consideration of risk factor. That’s why the next important step of exploration is developing of effective prophylactic measures for occupational injury prevention by definition of influence pattern on accidents which caused by technical, organizational, social, economic and manufacture reasons.
Keywords: safety and health at work; occupational injury; frequency of injury coefficient; partial loss of working capacity coefficient; injury heaviness coefficient; виробничий травматизм; нещасний випадок; безпека праці; коефіцієнт частоти травматизму; коефіцієнт часткової втрати працездатності; коефіцієнт тяжкості травматизму; производственный травматизм; несчастный случай; безопасность труда; коэффициент частоты травматизма; коэффициент частичной потери трудоспособности; коэффициент тяжести травматизма; кафедра екології та екоменеджменту